Brain Volumetric Measurements in Children With Attention Deficit Hyperactivity Disorder: A Comparative Study Between Synthetic and Conventional Magnetic Resonance Imaging - Chen, Yingqian; Su, Shu; Dai, Yan; Wen, Zhihua; Qian, Long; Zhang, Hongyu; Liu, Meina; Fan, Miao; Chu, Jianping; Yang, Zhiyun (Frontiers in Neuroscience, 2021)
Objective To investigate the profiles of brain volumetric measurements in children with attention deficit hyperactivity disorder (ADHD), and the consistency of these brain volumetric measurements derived from the synthetic and conventional T1 weighted MRI (SyMRI and cT1w MRI). Method Brain SyMRI and cT1w images were prospectively collected for 38 pediatric patients with ADHD and 38 healthy children (HC) with age range of 6-14 years. The gray matter volume (GMV), white matter volume (WMV), cerebrospinal fluid (CSF), non-WM/GM/CSF (NoN), myelin, myelin fraction (MYF), brain parenchyma volume (BPV) and intracranial volume (ICV) were automatically estimated from SyMRI data, and the four matching measurements (GMV, WMV, BPV, ICV) were extracted from cT1w images. The group differences of brain volumetric measurements were performed respectively using analysis of covariance. Pearson correlation analysis and interclass correlation coefficient (ICC) were applied to evaluate the association between synthetic and cT1w MRI derived measurements. Results As for the brain volumetric measurements extracted from SyMRI, significant decreased GMV, WMV, BPV and increased NON volume (p < 0.05) were found in ADHD group compared with HC; No group differences were found in ICV, CSF, myelin volume and MYF (p > 0.05). With regard to GMV, WMV, BPV and ICV estimated from cT1w images, the group differences between ADHD and HC were consistent with the results estimated from SyMRI. And these four measurements showed noticeable correlation between the two approaches (r = 0.692, 0.643, 0.898, 0.789 respectively, p＜0.001; ICC values are 0.809, 0.782, 0.946, 0.873 respectively). Conclusion Our study demonstrated the global brain development retardation but normal whole brain myelination in child with ADHD. Moreover, our results demostrated the high consistency of brain volumetric indices between synthetic and cT1w MRI in children, which indicate the high reliability of SyMRI in the children brain volumetric analysis.